(untitled) (Homoeopathy for All, 2022)
Hepatocellular Carcinoma (HCC) is the most common cause of liver cancer. It constitutes 90% of the global incidence of liver cancer. Worldwide, the 5thcommon cause of cancer affecting human life is hepatocellular carcinoma. Approximately 7 lakh deaths are caused by HCC and makes it 3rdcommon cause of death due to cancer.1 Several reports suggest that the incidence of HCC is increasing day by day. Indian data on the epidemiology of HCC is not clearly available. Data available by national cancer registry program and by International Agency for Research on Cancer (WHO) in 2008 male and female ratio for HCC is 4:1. According to data age, presentation is 40 to 70 years. The incidence rate ranges from 0.7 to 7.5 for males and 0.2 to 2.2 per 1 lakh population. According to another report, the incidence of HCC in cirrhotic liver conditions in India is 1.6% per year.2It has been reported from the studies that chronic viral hepatitis has an important role.3,4As per the data in India 15 million people are suffering from hepatitis C virus and 45 million people are suffering from hepatitis B virus infection.5,6 Intake of alcohol is increasing gradually in India. However, the possible role of chronic alcoholism and viral infection in the causation of HCC has not been assessed in detail, but some countries have reported a positive association.7,8,9 Asians are prone to develop Diabetes type II and DM is a risk factor for the HCC in India.10In the conventional medicine liver transplant, surgical resection for the patients of single nodules with good liver function, radiofrequency ablation, transarterial chemoemboliza tion or TACE for the patients with intermediate stage of HCC and radioembolization or selective internal radiation therapy (SIRT) are the recommended treatments.In India, homoeopathic treatment is an eminent alternate and complementary treatment. Homoeopathic medicines are found effective in tackling the condition and the side effects caused by conventional treatment and in managing the hopeless cases of HCC as an Integrative therapy. In this article, we discuss the scope of homoeopathy in treating HCC with scientific evidences.